Drivers of eco-innovation: empirical evidence from Slovenia. (2017) - Hojnik, Jana; Ruzzier, Mitja; Antončič, Boštjan
This paper uses a regression analysis to explore the determinants of eco-innovation, based on a sample of 80 Slovenian companies. The findings of this study are two-fold. First, the determinants of eco-innovation vary depending on the type of eco-innovation (product, process or organisational). The results reveal that customer demand and competitive pressure drive product eco-innovation, while managerial environmental concern, competitive intensity and competitive pressure spur process eco-innovation, and only competitive pressure exerted effect on organisational eco-innovation. Second, the findings indicate that competitive pressure is a common driver of all three eco-innovation types (product, process and organisational). Therefore, the results lead to the conclusion that different factors spur different eco-innovation types, while competitive pressure works as a common driver of all three eco-innovation types. Based on the results, we can infer that implementation of eco-innovations is becoming a relevant strategy for companies to establish a green image and pursue sustainability in this intense competitive environment.